A Population-Based Assessment of Urologic Procedures and Operations After Surgery or Pelvic Radiation for Cervical Cancer. Issue 5 (1st June 2018) - Welk, Blayne; Wallis, Christopher; D'Souza, David; McGee, Jacob; Nam, Robert K.
Abstract : Objective: The treatment of cervical cancer can result in genitourinary morbidity. We measured selected urologic procedures after the treatment of cervical cancer with either surgery or radiation. Methods: We used administrative data from the province of Ontario Canada to identify adult women who had nonmetastatic cervical cancer and were treated with surgery or radiation between 1994 and 2014. Study outcomes were surgical or procedure codes representing ureteric repair or fistula repair. Stress incontinence surgery, minimally invasive urologic procedures, open bowel/bladder surgeries, and secondary malignancy were measured to compare between treatment modalities. Multivariable Cox proportional hazards models were used. Results: Our final cohort consisted of 7311 women (median follow-up, 7.0 years [interquartile range, 2.9–13.3 years]), of which 3354 (44.9%) underwent radiation, and 3957 (54.1%) underwent surgery. After treatment of cervical cancer, ureteral repair was less common after surgery (3.4%) compared with radiation (10.3%) (hazard ratio [HR], 0.25; 95% confidence interval [CI], 0.19–0.32). Fistula repair was uncommon (0.9%) and occurred significantly more often in the surgery and radiation group compared with the radiation-alone group (HR, 4.02; 95% CI, 1.80–9.00). Overall, stress incontinence surgery was uncommon (2.2%) but was significantly more likely after surgery versus radiation (HR, 3.73; 95% CI, 2.13–6.53). Minimally invasive urologic procedures were less common after surgery compared with radiation (HR, 0.49; 95% CI, 0.44–0.54). Open bowel/bladder surgeries were similar among treatment modalities, and secondary malignancy was less common after treatment with surgery versus radiation (HR, 0.60; 95% CI, 0.39–0.92; P = 0.02). Conclusions: Women treated for cervical cancer undergo ureteral stricture interventions at 0.8% per year over the 20 years after their treatment; this risk is higher among women who receive radiation treatment. Fistula repair is rare after cervical cancer.